Design of Optimum Commercial Airline Fare Using a Hybrid Algorithm of AHP, DEMATEL-ANP and Goal Programming - Budi Sukoco, M. Dachyar, Farizal (International Journal of Advanced Science and Technology, 2020)
Designing airfare is a way to manage the competitiveness level and increase marketshare to enhance profitability. Implementation of a pricing strategy becomes veryimportant for the airline since determining its airfare is known as a very complex process.This research aims to find the optimum airfare based on the schedule in the tourist-baseddestination during peak season by sequential method comprised of Analytical HierarchyProcess (AHP), Decision-Making Trial and Evaluation Laboratory - Analytic NetworkProcess (D-ANP) and Goal Programming. The case study of this research applied to anIndonesian airline company